The Community Service (PKM) Aloe Vera Products Processing at North-Serpong District, South-Tangerang City - Muhammad Imam Muttaqijn; Tri Endi Ardiansyah PS (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This community service (PKM) shall focus on the economic affair, these are: first, aloe vera products processing such are hand-sanitizer and smoothing gel. Second, the management aspect by mentoring on packaging technique, market penetration, and business management. This activity introduced unassuming technologies such as automatic mixers, cookers, ordinary chemical compounds, and also digital business instruments. The program partner involved is the public unit Kampong Pancasila which was founded by Mrs. Hj. Muriah together with the PKM-UMT team. As long as, Mrs, Hj Muriah has been successful in developing the local aloe vera variety so that has owned the highest quality and has got worthiness to production. This program was conducted by using methods: a. Dialogue with the partner, b. workshop, c. Focus group Discussion (FGD), d. Program initiation, e. Activity method design, f. monitoring, and evaluation. Outcomes of this activity are management to the program partner and development to localSME based on aloe vera product processing such are hand-sanitizer and smoothing gel. Therefore, the program partner and local society could be developed economic resilience and increase the prosperity of the local society. Keywords: Communit